Learner-Centered Education: A Critical Approach To Student Development - Zanyar Nathir Ghafar (PT Publikasiku Academic Solution, 2024)
The learner-centred educational approach emphasizes active student participation and adapting teaching methods to each student's interests and needs. This study aims to analyze the impact of this approach on the development of students' self-reflection skills, knowledge acquisition, and collaboration within the classroom community. The research method used is qualitative with a descriptive approach, involving interviews, focus groups, and observations of students, educators, and administrative staff at a higher education institution implementing this learning approach. The study results indicate that the learner-centred approach can improve student engagement and learning outcomes despite challenges such as teacher training needs and varying student engagement. The conclusions of this study confirm that learner-centred education can create a more collaborative learning environment and support the development of students' holistic abilities, especially with the support of technology and significant cross-disciplinary interactions.